Unlocking Power of Phonics for Literacy: Revolutionizing Reading Literacy Skills Development through Phonics Technique in Non-Formal Basic Education Schools - Muhizma Kanwal (IJLTP, 2025)
This study was conducted to find out the effects phonic technique on students’ literacy skills (reading skills of English language) at primary level. Population of study comprised on all students at Non-Formal Basic Education Schools. By using cluster sampling technique, the researcher selected four Non formal basic education schools of village Nara (Attock). Total number of students involved in the experiment was 32. Sample students were distributed in two equal classes by pairing on the base of equal marks and mean score. Both classes were labelled as A and B. Class A, and B was randomly assigned to either experimental or control group. The pretest posttest control group design, that is, true experimental pretest post-test design was used. For the purpose of getting results a test was developed. Its items were selected after its validation from five experts. The reliability of test items was assessed through pilot study indicating .84* alpha reliability coefficient. In the test the researcher assessed four reading skills including phonemic awareness, vocabulary, fluency, and comprehension. The experimental group was taught using phonics and control group was taught using traditional techniques (read aloud and reading). Experiment was of one-month duration, and 26 lesson plans were developed. Time duration for each lesson plan was 40 minutes. Results were analyzed through t-test. Results showed that phonic technique had significant effects on students’ reading skills as compared to traditional techniques. So, it is recommended that English teachers may be trained and encouraged for using phonic technique and picture support technique in teaching English reading.